PERLINDUNGAN HUKUM TERHADAP PEKERJA MIGRAN INDONESIA INFORMAL MENURUT UNDANG UNDANG NOMOR 18 TAHUN 2017 TENTANG PERLINDUNGAN PEKERJA MIGRAN - Berkat Anugrah Kurunia Situmorang; Marzuki Marzuki; Ibnu Affan (Jurnal Ilmiah METADATA, 2021)
It is appropriate, the state guarantees rights, opportunities, and provides protection for every citizen without discrimination to get a job and decent money income, both at home and abroad in accordance with their expertise, skills, talents, interests and abilities. The formulation of the problem in this thesis is how to regulate informal Indonesian migrant workers according to Law Number 18 of 2017 concerning the Protection of Migrant Workers, how to protect informal Indonesian migrant workers according to Law Number 18 of 2017 concerning Protection of Migrant Workers, how are the obstacles in providing protection for migrant workers Informal Indonesia according to Law Number 18 of 2017 concerning the Protection of Migrant Workers and efforts to overcome it. The research method used is descriptive analysis which leads to normative juridical legal research, namely research carried out by referring to legal norms, namely examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results show that the regulation of the placement of Indonesian migrant workers is based on statutory regulations, namely Law 13 of 2003 concerning Manpower, Law of the Republic of Indonesia Number 18 of 2017 concerning Protection of Indonesian Migrant Workers, Regulation of the Minister of Manpower of the Republic of Indonesia Number 22 of 2014 concerning Implementation of Placement and Protection of Indonesian Workers Abroad. Protection of informal Indonesian migrant workers according to Law Number 18 of 2017 concerning the Protection of Migrant Workers and its derivative regulations are the guidelines for labor attaches and / or appointed foreign officials. However, this is not easy considering the complexities of protecting Indonesian migrant workers abroad, as well as things that may not be unexpected beforehand. The obstacle in providing protection for informal Indonesian migrant workers is the weakness of supervision in line with the governance structure between the central government, the Ministry of Manpower as the issuer of the license and the sectoral manpower office in the regions.